Critical Discourse Analysis of Imagine by John Lennon: An Iconic Song - Siti Mutiah Ulfha; Siti Lutfiah Rabiyatul Adawiyah; Saiful Anwar (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STAI Raudhatul Akmal, 2023)
Song lyrics will communicate several concepts, including saying something, conveying the author's experience and generating comments or opinions from listeners. Song lyrics are also the author's hidden messages or expressions of the author's heart. This study aims to describe the text analysis of Imagine by John Lennon and the elements of social cognition and context in the song. This research is library research with a qualitative descriptive method, and the approach used is the critical discourse analysis of Teun A. van Dijk. The research data is the lyrics of the song 'imagine' by John Lennon. This finding shows that the diction used in the lyric is cohesive and coherent to support the song's meaning. Moreover, social cognition has relation to the contemporary social context, the conflict between Ukraine and Russia.